2015
DOI: 10.3945/ajcn.113.076174
|View full text |Cite
|
Sign up to set email alerts
|

Fish consumption and risk of non–gallstone-related acute pancreatitis: a prospective cohort study

Abstract: Our data suggest that the consumption of total fish (fatty fish and lean fish combined) may be associated with decreased risk of non-gallstone-related acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…AP is characterized by an acute inflammation of the pancreas that results in a clinical spectrum ranging from the more common, mild and self-limiting course, to severe disease that is even associated with the risk of mortality [11]. While alcohol and gallstones are the two most common factors linked to the causation of an attack of AP [4,12e14], other associated causes include diet [15,16], drugs [17], pancreatic tumours and certain genetic predispositions [18].The habits of cigarette smoking and consuming alcohol quite often co-exist [19]. Hirota and colleagues [19] noted that alcoholic patients suffering from pancreatitis were more likely to smoke when compared to non alcoholics.…”
mentioning
confidence: 99%
“…AP is characterized by an acute inflammation of the pancreas that results in a clinical spectrum ranging from the more common, mild and self-limiting course, to severe disease that is even associated with the risk of mortality [11]. While alcohol and gallstones are the two most common factors linked to the causation of an attack of AP [4,12e14], other associated causes include diet [15,16], drugs [17], pancreatic tumours and certain genetic predispositions [18].The habits of cigarette smoking and consuming alcohol quite often co-exist [19]. Hirota and colleagues [19] noted that alcoholic patients suffering from pancreatitis were more likely to smoke when compared to non alcoholics.…”
mentioning
confidence: 99%
“…A Swedish cohort reported a protective association between fish consumption and non-GS AP 23 . The authors hypothesized that the protective association was due to the anti-inflammatory and antioxidative properties of the long chain n-3 polyunsaturated fatty acids found in fish 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The summary of each of these case reports of food-related acute pancreatitis has been provided in Table 1. Furthermore, several large multiethnic cohort studies have indicated that high dietary glycemic load, saturated fat, cholesterol, red meat, and eggs raise the risk of non-gallstone-related acute pancreatitis [27, 28]; In contrast, recent reports have indicated that the consumption of vegetables and fish (fatty and lean fish combined) may be associated with decreased risk of non-gallstone acute pancreatitis [29, 30]. The summary of prospective cohort studies related with food-induced acute pancreatitis in human was presented in Table 2.…”
Section: Food Allergen-induced Eosinophilic Gastroenteritis and Pancrmentioning
confidence: 99%
“…[28] were associated with the risk of non-gallstone-related acute pancreatitis. While other studies report that vegetables and fish (including fatty and lean fish) may be associated with decreased risk of non-gallstone acute pancreatitis [29, 30]. All these studies indicate that certain foods are associated with an increased risk of acute pancreatitis while other foods might be protective.…”
Section: Introductionmentioning
confidence: 98%